Structural and biochemical characterisation of human integral membrane proteins regarded as potential therapeutic targets - da Costa Cabral Gomes Páscoa, T (2022)
Integral membrane proteins are responsible for a wide range of cellular functions and are important targets for the development of novel therapeutics. Therefore, obtaining structural and mechanistic insights into their function is of central importance for rational drug design. In this thesis, I focused on characterising three human integral membrane proteins using X-ray crystallography, cryo-EM, mass spectrometry and other biochemical methods.